Chatbot Interactions and Customer Loyalty: Analyzing The Role of Personalization and Responsiveness - Mulyanto, Dody; Pradiska Budi, Agustyarum (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze the role of chatbots in enhancing customer loyalty by assessing how aspects such as personalization and responsiveness affect customer experience. The study sampled 250 respondents who use customer service in e-commerce companies in the city of Surakarta. The research employed multiple linear regression techniques. The results indicate that personalization and responsiveness in chatbot interactions are factors that play a positive and significant role in increasing customer loyalty. Quick and accurate chatbot interactions that align with customer needs can provide assurance and reduce uncertainty and customer frustration. This study is limited to examining the aspects of personalization and responsiveness in chatbot interactions concerning customer loyalty, and the scope of the research is restricted to customers in the city of Surakarta. Future research opportunities could explore other aspects beyond personalization and responsiveness and expand the research scope beyond just Surakarta.